Phyrochemical Screening and Potential Inhibition of Pacing Extract (Costus speciousus, J.Sm) Against Mycobacterium Tuberculosis H37Rv - Puspaningtyas, Ayik Rosita; Rumaikewi, Carolin Enjelin; Sari, Indah Purnama (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2024)
Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis (Mtb) and can attack various organs of the body. Transmission occurs through sputum splashes when coughing, sneezing or talking. TB treatment using antituberculosis drugs (OAT) can cause side effects that affect health. Therefore, alternative therapies from natural ingredients are needed. This study aims to explore secondary metabolites in extracts and plant fractions of Pacing (Costus speciousus, J.Sm) and determine their effectiveness against Mycobacterium tuberculosis H37Rv. The extraction method used is remaceration with methanol solvent. The concentrations of the samples tested varied with isoniazid positive controls. The results showed that Pacing plant extracts and fractions contained alkaloids, flavonoids, saponins, and tannins. Terpenoid compounds were not detected in the samples tested. The antituberculosis test showed that the n-hexane fraction had the best anti-TB activity, although the IC50 value of the extract and fraction was still lower than isoniazid as a positive control. However, Pacing extract and fraction still have potential as very strong anti-TB agents because their IC50 values ​​are below 50 ppm.